Generation of Insulin-Producing Cells from Canine Adipose Tissue-Derived Mesenchymal Stem Cells - Takahiro Teshima; Keiji Okamoto; Kazuho Dairaku; Tomokazu Nagashima; Masaki Michishita; Ryohei Suzuki; Hirotaka Matsumoto; Hidekazu Koyama (Stem Cells International)
The potential of mesenchymal stem cells (MSCs) to differentiate into nonmesodermal cells such as pancreatic beta cells has been reported. New cell-based therapy using MSCs for diabetes mellitus is anticipated as an alternative treatment option to insulin injection or islet transplantation in both human and veterinary medicine. Several protocols were reported for differentiation of MSCs into insulin-producing cells (IPCs), but no studies have reported IPCs generated from canine MSCs. The purpose of this study was to generate IPCs from canine adipose tissue-derived MSCs (AT-MSCs) in vitro and to investigate the effects of IPC transplantation on diabetic mice in vivo. Culturing AT-MSCs with the differentiation protocol under a two-dimensional culture system did not produce IPCs. However, spheroid-like small clusters consisting of canine AT-MSCs and human recombinant peptide μ-pieces developed under a three-dimensional (3D) culture system were successfully differentiated into IPCs. The generated IPCs under 3D culture condition were stained with dithizone and anti-insulin antibody. Canine IPCs also showed gene expression typical for pancreatic beta cells and increased insulin secretion in response to glucose stimulation. The blood glucose levels in streptozotocin-induced diabetic mice were decreased after injection with the supernatant of canine IPCs, but the hyperglycemic states of diabetic mice were not improved after transplanting IPCs subcutaneously or intramesenterically. The histological examination showed that the transplanted small clusters of IPCs were successfully engrafted to the mice and included cells positive for insulin by immunofluorescence. Several factors, such as the transplanted cell number, the origin of AT-MSCs, and the differentiation protocol, were considered potential reasons for the inability to improve the hyperglycemic state after IPC transplantation. These findings suggest that canine AT-MSCs can be differentiated into IPCs under a 3D culture system and IPC transplantation may be a new treatment option for dogs with diabetes mellitus.